Impact of Home science training on Rural Women - Kumari, Maya; Kumar, Ashok; Prasad, Pradeep; Kumar, Shashi Bhushan (Indian Journal of Extension Education, 2009)
The human resource of country is highly significant and its development is essential for the progress and prosperity of the nation. Women constitute half of the population of the country. Their contribution to economy has become obvious that they are the pivot around whom the family, the society and whole humanity moves. However, their contribution is not well recognized and valued. Of course, in recent past a number of programmes and activities have. been undertaken to ameliorate this vulnerable section of population. But we have to yet go 'miles and miles together for the empowerment of women in real sense and spirit. In order to strengthen them and improve their status there is need to increase their participation in income generating activities.